2019
DOI: 10.3748/wjg.v25.i27.3619
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative diffusion-weighted magnetic resonance enterography in ileal Crohn's disease: A systematic analysis of intra and interobserver reproducibility

Abstract: BACKGROUND Magnetic resonance enterography (MRE) is increasingly attractive as a noninvasive and radiation-free tool for assessing Crohn’s disease (CD). Diffusion-weighted imaging (DWI) is recommended as an optional MRE sequence for CD by the European Society of Gastrointestinal and Abdominal Radiology, and has shown a superb potential as a quantitative modality for bowel inflammation evaluation. However, the measurement reproducibility of quantitative DWI analysis in MRE has not been ascertained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“… CE T1w MRE can be replaced by DWI. Yu, 2019 [67] DWI and ADC ileocolonoscopy terminal ileum active inflammation n/s ADC and ileum to psoas signal SR both showed high reproducibility (ICC=0.952 and ICC=0.969) ADC: 85.7% Sens and 95.7% Spec SR: up to 95.2% Sens and 95.7% Spec SR and ADC values can quantitatively diagnose the presence of active CD lesions. SR has better sensitivity.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… CE T1w MRE can be replaced by DWI. Yu, 2019 [67] DWI and ADC ileocolonoscopy terminal ileum active inflammation n/s ADC and ileum to psoas signal SR both showed high reproducibility (ICC=0.952 and ICC=0.969) ADC: 85.7% Sens and 95.7% Spec SR: up to 95.2% Sens and 95.7% Spec SR and ADC values can quantitatively diagnose the presence of active CD lesions. SR has better sensitivity.…”
Section: Resultsmentioning
confidence: 92%
“…ROC: the receiver operating characteristics. Study Reference test ADC threshold ( /s) AUC Sensitivity Specificity Yang, 2019 [42] ileocolonoscopy 0.87 0.924 0.906 0.936 Li, 2015 [19] clinical score 1.12 0.98 1 0.88 Strakšyte, 2020 [60] ileocolonoscopy 1.32 0.883 0.979 0.978 Abd-El Khalek, 2018 [72] CE-MRE 1.38 n/s 0.93 0.9 Schmid-Tannwald, 2016 [79] histopathology 1.41 0.95 0.93 0.75 Soydan, 2019 [68] ileocolonoscopy 1.47 0.729 0.885 0.657 Huang, 2018 [41] CE-MRE 1.485 0.907 0.864 0.9 Stanescu-Siegmund, 2017 [76] CE-MRE, clinical scoring 1.56 0.998 0.974 0.992 Li, 2017 [75] ileocolonoscopy 1.59 0.974 0.972 0.843 Yu, 2019 [67] ileocolonoscopy 1.81 0.929 0.857 0.957 Hordonneau, 2014 [88] CE-MRE 1.9 n/s 0.937 ...…”
Section: Resultsmentioning
confidence: 99%
“…The quality of DWI images is therefore lesser than that of conventional MR images, due to low resolution, noise, distortions, and limited morphological interpretability (Chilla et al, 2015); therefore, DWI provides functional rather than anatomical information. Opinions on reproducibility of ADC-DWI measurements used in the Clermont score varies among authors, and despite good to excellent repeatability reported from certain authors (Yu et al, 2019), contrary concerns on low reproducibility based on research data also exist (Watson et al, 2018). Due to equivocal data on repeatability of measurements the form the MaRIA and Clermont score, our interest was to assess the repeatability of measurements contributing to both of these indices -WSI-preGd and WSI-postGD forming RCE in MaRIA, ADC-DWI used in the Clermont score, as well as bowel thickness and estimation of presence of bowel ulcers, which are common to both MaRIA and Clermont scores.…”
Section: Discussionmentioning
confidence: 99%
“…Einige Studien haben sich mit der DWI als potenziellem Biomarker beschäftigt, und es wurde versucht, potenzielle "Apparent-diffusion-coeffi- cient"(ADC)-Grenzwerte zu definieren, mit deren Hilfe evtl. zwischen unterschiedlichen Stadien der Entzündung differenziert werden kann [2,39]. Anhand dieses Prinzips kann das DWI auch zur Beurteilung des Therapieansprechens hilfreich sein [12].…”
Section: Entzündungsstadienunclassified